Structure, Preparation, and Applications of 2D Material‐Based Metal–Semiconductor Heterostructures. Issue 1 (25th November 2020) - Tan, Junyang; Li, Shisheng; Liu, Bilu; Cheng, Hui-Ming
Abstract : Two‐dimensional (2D) materials' family with its many members and different properties has recently drawn great attention. Thanks to their atomic thickness and smooth surface, 2D materials can be constructed into heterostructures or homostructures in the fashion of out‐of‐plane perpendicular stacking or in‐plane lateral stitching, resulting in unexpected physical and chemical properties and applications in many areas. In particular, 2D metal–semiconductor heterostructures or homostructures (MSHSs) which integrate 2D metals and 2D semiconductors, have shown great promise in future integrated electronics and energy‐related applications. Herein, MSHSs with different structures and dimensionalities are first introduced, followed by several ways for their preparation. Their applications in electronics and optoelectronics, energy storage and conversion, and their use as platforms to exploit new physics are then discussed. Finally, the perspectives about the challenges and future research directions in this emerging field are given. Abstract : 2D material‐based metal–semiconductor heterostructures (MSHSs) have drawn great attention due to their unexpected physical and chemical properties and applications in many areas. The latest research progress in the structure, preparation, and applications of 2D material‐based MSHSs are presented. Furthermore, the perspectives about the challenges and future research directions in this emerging field are given.